3D Printed Interposer Layer for High Density Packaging of IoT Devices - Mondal, S; Ghazali, MIM; Wijewardena, K; Kumar, D; Chahal, P (IEEE, 2024)
3D printing has emerged as a potential solution to fabricate different RF components and embed prepackaged devices. In this work, 3D printed interposer layer is proposed to enable vertical stacking of different heterogeneous components and substrates. Different design parameters were first simulated using HFSS to optimize for maximum possible bandwidth. After optimization, the design parameters were used to fabricate a wireless battery less digital modulator as an example IoT device. Measurement results are provided to validate the design and simulation results.